Infrared wireless tracking device for human motion sensing / Azman Hilmi Mohd Zaili - Mohd Zaili, Azman Hilmi (2011)
This article presents an infrared wireless tracking device for human motion sensing. An infrared LED is fabricated; the IR-pen and IR-head device. The IR-pen and IR-head device signab will be detected by the Wiimote and webcam and followed by transferring the signal to the computer via simulation application program. Basic principle of the Wiimote is studied and had been implemented on the flight simulation program. The accuracy of the BR-motion via Wiimote and webcam is then compared to determine the efficiency for real-life human motion sensing used in many aviation academies. The result shows that the Wiimote has the high accuracy in capturing the infrared signal thus it fulfills the requirement of human motion sensing.